One for the Team: Domestic Violence Scandals and Reflexive Media Commentary by Rugby League Players in Australia. (February 2018) - Packard Hill, Esther; Fuller, Glen
In the decade 2005–2015, National Rugby League players were implicated in a variety of off-field instances of violence against women. These incidents have been covered heavily by the Australian media and have facilitated commentary on violence and sport, rugby league culture, and whether rugby league players have a propensity for violence. From a total corpus of 933 articles, we critically engage with 190 news reports of domestic violence and focus on the way players and others contribute to media commentary about the incidence of domestic violence allegedly perpetrated by their teammates. Our guiding research question is: What is the character of public commentary expressed by rugby league players about incidents of domestic violence involving teammates? We identify four modes of reflexive commentary involving teammate representation that occur in the reporting of rugby league players accused of domestic violence offences. We argue that these four modes of representation articulate greater or lesser degrees of support or criticism between teammates about domestic violence and, even when critical, these discourses work to rearticulate the normative diminished reflexivity afforded men to publicly comment on and about other men.